Exploring the House Burglar's Perspective: Observing and Interviewing Offenders in St. Louis, 1989-1990 - Wright, Richard ([Verlag nicht ermittelbar], 1994)
These data investigate the behaviors and attitudes of active residential burglars, not presently incarcerated, operating in St. Louis, Missouri. Through personal interviews, information was gathered on the burglars' motivation and feelings about committing crimes, peer pressure, burglary methods, and stolen goods disposal. Respondents were asked to describe their first residential burglary, to recreate verbally the most recent residential burglary they had committed, to discuss their perceptions of the risk values involved with burglary, and to describe the process through which they selected potential targets for burglaries. In-depth, semistructured interviews lasting from one and a half to three hours were conducted in which participants were allowed to speak freely and informally to the investigator. These interviews were tape-recorded and transcribed verbatim, and some were later annotated with content-related markers or "tags" to facilitate analysis. Information was also elicited on age, race, sex, marital status, employment status, drug history, and criminal offense history.